Association between nutritional status and dengue severity in Thai children and adolescents. - Haypheng Te; Pimolpachr Sriburin; Jittraporn Rattanamahaphoom; Pichamon Sittikul; Weerawan Hattasingh; Supawat Chatchen; Salin Sirinam; Kriengsak Limkittikul (Public Library of Science (PLoS), 2022)
Most cases of dengue virus infection are mild, but severe cases can be fatal. Therefore, identification of factors associated with dengue severity is essential to improve patient outcomes and reduce mortality. The objective of this study was to assess associations between nutritional status and dengue severity among Thai children and adolescents. This retrospective cross-sectional study was based on the medical records of 355 patients with dengue treated at the Hospital for Tropical Disease (Bangkok, Thailand) from 2017 to 2019. Subjects were Thai children aged less than 18 years with dengue virus infection confirmed by positive NS1 antigen or IgM. The 1997 and 2009 World Health Organization (WHO) dengue classifications were used to define disease severity and body mass index for age while the WHO growth chart was used to classify nutritional status. The proportions of patients with dengue fever who were underweight, normal weight, and overweight were 8.8%, 61.5%, and 29.7%, respectively. The proportions of patients with dengue haemorrhagic fever (DHF) who were underweight, normal weight, and overweight were 10.2%, 66.1%, and 23.7%, respectively. The proportions of patients with non-severe dengue who were underweight, normal weight, and overweight were 8.6%, 60.9%, and 30.5%, respectively; the same proportions of patients with severe dengue were 10.5%, 67.1%, and 22.4%, respectively. Higher proportions of patients with severe plasma leakage (DHF grade III and IV) were overweight compared with those with mild plasma leakage (DHF grade I and II) (45.5% vs. 18.8%). No difference in nutritional status was observed in patients with different dengue severity.